Clinical benefits of TNF‐α inhibitors in Chinese adult patients with NLRP3‐associated autoinflammatory disease. (12th June 2021) - Wu, N.; Wu, D.; Zhao, M.; Miao, J.; Yu, W.; Wang, Y.; Shen, M.
Abstract: Background: Nucleotide‐binding oligomerization domain‐like receptor family, pyrin domain containing 3 ( NLRP3 )‐associated autoinflammatory disease ( NLRP3 ‐AID) is a rare, heterogeneous disease entity associated with mutations in NLRP3 . Biologic therapy for NLRP3 ‐AID yields diverse results. Objectives: We aimed to evaluate the clinical features and outcomes of Chinese adult patients with NLRP3 ‐AID who were treated with tumour necrosis factor (TNF)‐α inhibitors. Methods: Five patients with NLRP3 ‐AID were diagnosed and treated with TNF‐α inhibitors at Peking Union Medical College Hospital between 2017 and 2020 and were followed up for 6 to 12 months. All patients were systematically studied for treatment outcomes, including clinical manifestations and inflammatory markers. Results: All five adult NLRP3 ‐AID patients were Chinese Han, and four patients were males. The mean age at disease onset was 4.2 ± 4.1 years, and the mean time of diagnosis delay was 19.8 ± 6 years. All patients received TNF‐α inhibitors with or without methotrexate/prednisone. During follow‐up, all patients achieved remarkable clinical remission of skin lesions and polyarthritis and showed improvements in acute‐phase reactants, inflammatory cytokines, patient visual analogue scale, physician global assessment and 36‐item Short Form (SF‐36). Conclusions: Early diagnosis and effective therapy for NLRP3 ‐AID are essential for avoiding irreversible organ damage. TNF‐α inhibitors might serve as a therapeutic alternative for patients with NLRP3 ‐AID who have unsatisfactory responses or no access to interleukin‐1 inhibitors. Abstract :